5. Efektifitas Penambahan Glyersol dalam Susu Pengencer terhadap Prosentase Sperma Hidup dan Penetasan Telur Ikan Mas (Cyprinus carpio Linn). - Linayati Linayati; Fadjar Basuki; Pinandoyo Pinandoyo (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2016)
To produce certain quality germ of goldfish artificial fertilization is made. The obstacle is insufficient fish sperm becauseof inadequate male mather and the gonad which arent simultaneously mature. To solve this problem, the fish sperm is stored by using thinning agent. The agent has to sustain sperm life during the storage. One of the medium is glycerined-milk. The research aims to find out the effect of glyserine with different concentration on thining milk to sperm motility and percentage of eggs hatching. Different glyserine concentration treatments are A) 0% B) 1% C) 3% D) 4%. After three days storage, the sperm motility is done by using microscope. The result show that variety of glyserine concentration in thinning milk give obvious effect to sperm motility percentage, fertility percentahe, and egg hatching. The highest sperm motility percentage obtained by treatment D (96,28 %) followed C 95.68 %, B (91,90 %), A (90,48), and E (89,04). The percentage of Fertilization are D,B,A,E with result 97,44 %, 94,64%, 90,92%, 89,91 %, 89,32 % respectively. The percentage of hatching are D (86.85 %), C (85.41%), B (84,23), A (83,73) and E (78,16). The water quality during research is still on the reasonable range to egg hatching. Keyword: sperm, glycerol, goldfish